Deodorization of Egg White Powder by Ozone Treatment and Underlying Mechanism - XIN Xiaojuan, LIU Ying, MA Lulu, HUO Jiaying, GAO Ying, DONG Shijian, LIU Liya, WANG Fengzhong, LI Shugang (Shipin Kexue)
This study investigated the effects of different ozone treatment times (0, 10, 20, 30, 40, and 50 min) on off-flavor removal from egg white powder (EWP) and the underlying mechanism. Results showed that compared with the untreated group (0 min), ozone treatment reduced the contents of the characteristic off-flavor substances (geranyl acetone, 1-octen-3-ol, octanal, and nonanal) in EWP by more than 40.94%. The sensory off-flavor score reached its lowest point (which decreased by 75% compared with the untreated group) after 20 min of ozone treatment, when egg white protein was slightly oxidized, leading to protein unfolding and structural disordering, increased carbonyl content and particle size, and decreased endogenous fluorescence intensity. In addition, fluorescence quenching and molecular docking showed that the major binding force between egg white protein and off-flavor substances was hydrophobic interaction, and their main binding sites were in a hydrophobic cavity composed of amino acids such as Leu66, Lys69, Glu87E, Ala87F, Cys87H, Glu129, Tyr130, Cys133, and Gly320. Ozone treatment for 20 min reduced the hydrophobic interaction between egg white protein and off-flavor substances by 45.98% compared with the untreated group, releasing off-flavor substances and reducing sensory off-flavor score, thereby ultimately deodorizing EWP. In conclusion, ozone treatment can reduce the off-flavor of EWP, the most pronounced effect being observed after 20 min treatment.